Elsie Gregory MacGill: Engineer, Feminist and Advocate for Social Change - Sissons, Crystal (Atlantis, 2009)
Elsie Gregory MacGill was a strong advocate for social change, and as a pioneering Canadian engineer and a feminist, her actions as a social activist during the 1960s and 1970s were influenced by and reflect this dual identity. Her actions also call into question the assumption that engineering and feminism are an unlikely combination.